Constraints Analysis of Village Panchayat Members in Their Job Performance in Banaskantha District of Gujarat State (Indian Journal of Extension Education, 2015)
The present study was conducted in Banaskantha district of Gujarat state. Palanpur and Dantiwada talukas were selected randomly. All the 20 samras village panchayats of both the selected talukas were selected purposively. The Panchayat members from each village were selected using proportionate random sampling technique making a sample of 120 panchayat members as respondents. The constraints experienced by village panchayat members were assessed against five aspects. The constraint perceived as hindering the job performance was rated by the respondents on a three point continuum viz., very effective, moderately effective and less effective with scores of 3, 2 and 1, respectively. Further for identifying the overall important constraints and aspects-wise important constraints, the total weighted score for each constraint were computed. The most important constraints in job performing of the village panchayat members having mean score more than the overall mean score (2.14) in order of importance were; ’inadequate fund allotted from government for development work’, ’lack of training to the village panchayat members’, ’delay in sections from upper authority’, ’lack of honorarium to the panchayat members working at village level’, ’lack of knowledge regarding PRS and development programmes’, ’no work initiated without giving bribe’, ’lack of administrative and financial power to the village panchayat members’, ’lack of experience as leader’, ’lack of information regarding different rural development programmes’, ’groupism encouraged by members’, ’lack of communication facility at village level’, ’low level of education’. The important suggestions endorsed by the village panchayat members were; ’amount of grant should be increased’, ’training on village developmental activities should be provided to village panchayat members’, ’training on leadership development and functioning of PRIs should be provided to village panchayat members’, ’office procedure should be more quick, easy and in time’ and ’honorarium should be given to village panchayat members’.